(3MW GdfbGH HYO QaY GdMLGH Yf hLhg CYeGd GdMSGHs - (3GdbGVj eMeO Hf RcQjG GdZQfGWjs
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA HGH GdLeY hgh GdHGH GdKGfi ef GdLRA GdChd s
(3BNQgG (B:s
(3jfJgi ChGFd GdLRA GdKGfi ef GdSaQ GdKGfi ai GdbhGfjf GdJi jecf GdhUhd HgG Edi GdeLghd s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP eMeO Gdefhfi HGdQHGW ef GdecJHGJ GdNGUI s
Keywords: (3GdQjGVjGJs